I Selfie Therefore I Exist: A Preliminary Qualitative Research on Selfie as Part of Identity Formation in Adolescents - Gita Widya Laksmini Soerjoatmodjo (Humaniora, 2016)
Selfie is a self-generated, self-selected picture to communicate the transitory message about oneself at a particular moment in time taken to be immediately distributed to others via social media networks. For adolescents, selfie becomes an online tool to explore and discover their identity throughout identity formation phase. Article aimed to address its purpose of describing the reasons why adolescents took selfies, what selfie mean to them and the meaning of others' responses on their selfies. Through textual analysis conducted upon written answers in a course exercise provided by 40 first semester students aged 18-20 years who participate in Introduction to Communication Technology course in Pembangunan Jaya University. This preliminary qualitative research concludes that they take the selfie as an activity done in their spare time to express themselves and to record memorable moments. For them, selfie means as their means for self-expression and as mementos. Others’ responses to their selfies gave them the affective feeling of approval. As these findings resonate with identity formation in adolescence, the theoretical implication is the need to continue exploring selfie as a means for the search of the identity. The practical implication of these findings is to use selfie and its future consequences with adolescence, including the issues of online safety and privacy.